Alternatif Penanggulangan Masalah Longsoran Tebing (Studi Kasus Lereng Km 20+300 Ruas Tol Pekanbaru-Kandis-Dumai) - handoko, yohan; Lastiasih, Yudhi; Mochtar , Indrasurya Budisatria (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
The Pekanbaru-Kandis-Dumai Toll Road passes through a hilly topography with steep valleys. In April 2024, a landslide occurred at Station 20+300, disrupting toll road traffic towards Pekanbaru. This condition forces the toll road to be cut and follow the contours to obtain both horizontal and vertical alignments. The purpose of this study was to determine the cause of the landslide and to find alternative repair methods using Geo5 analysis with two methods: crack soil approaches.The results of the analysis of existing conditions with the conventional method, the safety factor value is 1.082 and the crack soil method obtained a value of 0.882. After being reinforced with secant piles, the static safety factor value is 1.56 and the earthquake safety factor value is 1.122.